2020
DOI: 10.1021/acs.cgd.0c01368
|View full text |Cite
|
Sign up to set email alerts
|

Sr6(Li2Cd)A4S16 (A = Ge, Sn): How to Go beyond the Band Gap Limitation via Site-Specific Modification

Abstract: Band gap tuning is at the core of current optical and electronic device applications, the wide-band-gap chalcogenides are especially challenging and highly desired in many fields, such as nonlinear optical materials. On the basis of our in-depth investigation on the complicated cubic AII 6(BI 2CII)­DIV 4S16 family, we reveal that the structural complexity causes the band gap tuning to be determined by multiple factors, in which a “bucket effect” is uncovered. Guided by such a bucket effect strategy, we rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…When there is a significant difference between the E g s of the binaries M II Q and M IV Q 2 (Δ E g >0.5 eV), the one carries the lower E g acts as the shortest board, and eventually determines the E g of the quaternary. A similar “bucket effect” is widely found for the complex cubic A II 6 (B I 2 C II )D IV 4 S 16 family [15] …”
Section: Figuresupporting
confidence: 71%
“…When there is a significant difference between the E g s of the binaries M II Q and M IV Q 2 (Δ E g >0.5 eV), the one carries the lower E g acts as the shortest board, and eventually determines the E g of the quaternary. A similar “bucket effect” is widely found for the complex cubic A II 6 (B I 2 C II )D IV 4 S 16 family [15] …”
Section: Figuresupporting
confidence: 71%
“…Nonlinear optical (NLO) crystals are one type of crucial materials in all-solid-state lasers with the properties of frequency conversion and broadening the output spectral range and hence have attracted broad attention in recent years. , Generally, researchers classify NLO materials into several subgroups, including infrared (IR), ultraviolet–visible (UV–vis), and deep ultraviolet (DUV), according to the serving regions. In terms of IR NLO materials, metal chalcogenides are the most promising candidates due to their advantages in diverse noncentrosymmetric (NCS) structures, wide IR transmittance ranges, strong NLO responses, and favorable single-crystal growth habits, as shown by the commercial IR NLO materials AgGaS 2 (AGS) and AgGaSe 2 (AGSe). , Because of the increasing demands in laser technology and the disadvantages of the current commercial IR NLO materials (two-photon absorption of a 1 μm pumping laser for AGSe and low laser-induced damage threshold (LIDT) for AGS and AGSe), some metal chalcogenides with large band gaps, high SHG coefficients ( d ij ), large LIDT, phase matchability, and favorable single-crystal growth habits, such as BaGa 4 S 7 , BaGa 4 Se 7 , , BaGa 2 GeS 6 , and BaGa 2 GeSe 6 , have been regarded as new-generation IR NLO materials. However, the research involving these materials has been focused in laboratories, since they are usually obtained by small-scale reactions.…”
Section: Introductionmentioning
confidence: 99%
“…15 The absence of attractors capping Sn atoms also confirmed that the oxidation state of Sn is 4+. 15 The 2.34 Å Sn−S interactions show the strongest 50 There are many factors contributing to the LDT of crystalline solids. The LDT has two parts: dielectric and thermal LDT.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…), trivalent M 3+ (Al, In, Ga, etc. ), tetravalent M 4+ (Si, Ge, Sn), and pentavalent M 5+ (Sb); Ch = S, Se], which have demonstrated an excellent balance of NLO properties originating from their chemical flexibility. Recently, another system, II 6 I 4 V 4 Ch 16 (II = Sr, Ba; I = Li, Cu, Ag; IV = Ge, Sn; Ch = S, Se), has been heavily studied because of their emerging NLO properties and the demonstration of their excellent chemical flexibility. In this work, we discovered another seven compounds belonging to the II 6 I 4 V 4 Ch 16 (II = Sr, Ba; I = Li, Cu, Ag; IV = Ge, Sn; Ch = S, Se) family. The chemical flexibility of the II 6 I 4 V 4 Ch 16 (II = Sr, Ba; I = Li, Cu, Ag; IV = Ge, Sn; Ch = S, Se) family is further expanded on with the discovery of trivalent dopants for the first time.…”
Section: Introductionmentioning
confidence: 96%